Parental Acculturation and Children’s Bilingual Abilities: A Study With Chinese American and Mexican American Preschool DLLs - Uchikoshi, Yuuko; Lindblad, Mayu; Plascencia, Cecilia; Tran, Helen; Yu, Hallie; Bautista, Krystal Jane; Zhou, Qing (Frontiers in Psychology, 2022)
Previous studies support the link of parental acculturation to their children’s academic achievement, identity, and family relations (Baker, 2018). Prior research also suggests that parental language proficiency is associated with children’s vocabulary knowledge (Quiroz et al., 2010). However, few studies have examined the links of parental acculturation to young children’s oral language abilities. As preschool oral language skills have been shown to predict future academic achievement (e.g., Hammer et al., 2014; Mesa & Yeomans-Maldonado, 2019; Snow et al., 1998), it is critical to understand the relations between parental acculturation and bilingual abilities with young immigrant children. Furthermore, few studies have examined the links between parental acculturation and children’s bilingual ability among different immigrant groups who live in the same areas to understand possible similarities and differences. To address these gaps, this study examines these relations in two of the largest and fastest-growing immigrant populations in the U.S., Chinese American and Mexican American families (Park et al., 2017). A total of 119 dual language learners (DLLs; 64 Chinese Americans and 55 Mexican Americans) enrolled in Head Start programs in Northern California were recruited. DLLs were assessed on oral language measures in both their heritage language (HL) and English. Parental interviews were conducted to obtain parental acculturation and language proficiency. Results showed no significant group differences between Chinese American and Mexican American parents on the majority of their acculturation dimensions. Furthermore, there were no significant group differences in the bilingual abilities between Chinese American and Mexican American DLLs. Cluster analysis identified four groups of DLLs based on their bilingual ability: high language ability in both English and HL, low language ability in both, English-dominant, and HL-dominant. Results suggest that parental acculturation levels are more similar than different among the four groups. On average, parents in all four groups had stronger ties to their heritage culture and HL than to the American culture. Results also showed links between parental cultural identities and children’s language dominance. Parents of English-dominant children had significantly higher levels of American identity than the parents of children with high ability in both languages. Implications are discussed.